"God Brought Me Here to Change Me": Narratives of Spiritual Transformation in Pentecostal Migrant Churches in Norway. (5th September 2018) - Eriksen, Stian
Abstract : This article discusses narratives of spiritual transformation among Filipino migrants in the context of a Filipino Pentecostal migrant church in Norway, asking how Filipino migrants encounter and make use of religion in their migratory trajectories and experiences. The article takes a narrative approach to stories of transformation and discusses these with insights from theology, psychology and sociology of religion and in light of their sociocultural and spiritual contexts. The analysis focuses on these migrants' encounters, emotions and engagements related to facing life in Norway in context of the Pentecostal spirituality found in one growing Filipino migrant church. The article takes special interest in references to emotion as a hermeneutical cue in the narratives. From this, special attention is given to the individual's story and for understanding such churches as sociocultural and spiritual communities of transformation and mission.